Implementación de un módulo didáctico para entrenamiento de comunicaciones industriales para la carrera de Electromecánica de la UTC Extensión La Maná. - Avalos Aguaiza, Diego Fernando (2024)
The objective of this project is the implementation of a didactic module that consists of industrial communications training for the Electromechanics major and is located in the automation laboratory at the Technical University of Cotopaxi to improve the efficiency of the industrial communications learning system. The PLC Programmable Logic Controller allows precise control and greater diagnostic capacity, while the three-phase motor provides greater energy efficiency and power. In addition, the module has an HMI (Human-Machine Interface) that uses a graphical interface to allow teachers and students to interact with industrial equipment and processes, thus allowing them to perform tasks such as changing parameters and starting and stopping processes. The Module has a 35¨-plasma screen that provides visual information about the status of the equipment and allows students to better learn to control and monitor industrial processes. The combination of electrical control and an HMI and plasma screen allows for more efficient and safer learning management of industrial processes, thus reducing human errors and being able to develop the techniques and skills of future Electromechanical Engineering professionals.